Effect of Ethanolic Extract of Solanum torvum Leaf on Liver of Treated Rats: A recent study approach - Nweke Elizabeth Obioma; Nwizu Olive Ogechi (Challenges and Advances in Pharmaceutical Research Vol. 5, 2022)
Solanum torvum is a commonly used herb in traditional medicine. The aim of this study was to evaluate the effect of ethanol extract of Solanum torvum leaf on the liver of treated Wistar rats. Freshly harvested leaves of S.torvum were shade dried and ground to fine powder. 500 g of powdered plant sample was macerated in ethanol for 72 hrs. Adult male Wistar rats weighing 150-200 g were admistered with extract. Animals were slaughtered, and then blood and tissue samples were taken, extracted, and analysed according to standard protocols. The findings of this study demonstrate that administration of an aqueous extract of S. torvum boosted liver enzyme activity as well as levels of total and conjugated bilirubin in a dose-dependent way. However, there was no difference between the 100 mg/kg of S. torvum extract and the control in terms of enzyme activity and the levels of conjugated and total bilirubin (P>0.05). It can be concluded that Solanum torvum which is conventionally considered safe for human consumption could be hepatotoxic at high doses.